2018
DOI: 10.1007/s12046-018-0794-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient document-image super-resolution using convolutional neural network

Abstract: Experiments performed by us using optical character recognizers (OCRs) show that the character level accuracy of the OCR reduces significantly with decrease in the spatial resolution of document images. There are real life scenarios, where high-resolution (HR) images are not available, where it is desirable to enhance the resolution of the low-resolution (LR) document image. In this paper, our objective is to construct a HR image, given a single LR binary image. The works reported in the literature mostly deal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…We are addressing the problem of SISR for a task distinctly different from the above papers: to enhance the quality of the input binary document images so that the generated images have better readability and OCR accuracy. Our work builds on what has been reported in [46] [47], which addresses the above mentioned problem for the first time and is able to obtain good PSNR, OCR character and word level accuracies starting from a downsampled version of the document image (gray in nature), the results being similar to that of the corresponding ground truth image. In the current work, we have addressed the realistic problem of obtaining an upscaled version of a binary document image, actually scanned at a low resolution.…”
Section: Related Workmentioning
confidence: 82%
“…We are addressing the problem of SISR for a task distinctly different from the above papers: to enhance the quality of the input binary document images so that the generated images have better readability and OCR accuracy. Our work builds on what has been reported in [46] [47], which addresses the above mentioned problem for the first time and is able to obtain good PSNR, OCR character and word level accuracies starting from a downsampled version of the document image (gray in nature), the results being similar to that of the corresponding ground truth image. In the current work, we have addressed the realistic problem of obtaining an upscaled version of a binary document image, actually scanned at a low resolution.…”
Section: Related Workmentioning
confidence: 82%
“…A second popular approach has been to use super-resolution (for example, [7], [1], [8], [9] and [10]). This approach was also perhaps partially spurred on by the ICDAR 2015 Competition on Text Image Super-Resolution ( [11], [12] and [13]), which aimed to recognise text from frames extracted from video streams.…”
Section: Related Workmentioning
confidence: 99%
“…There has been considerable success with this method. For example, Pandey et al [9] reported OCR results for 75 dpi English text as 75.1% CLA (character level accuracy) and 48% WLA (word level accuracy). They achieved significantly better results on 75 dpi Tamil (90.8% CLA and 54.3% WLA) and Kannada (95.16% WLA and 70.80% WLA).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the advent of deep learning technologies in the past decade, superresolution algorithms have shown remarkable improvement in the quality of the reconstructed image. Most of the work reported in the literature have used mean square error (MSE) loss function to minimize the error between the reconstructed model output and the ground truth image [2] [3] [4] [5] [6] [7]. Minimizing this loss function may reduce the high frequency content in the reconstructed image and thus may blur the edges in it.…”
Section: Introductionmentioning
confidence: 99%